Validation of caspase-independent cell death inducing properties of geranylated 4 phenylcoumarins isolated from Mesua elegans on prostate cancer cell lines / Hani Sapili - Hani , Sapili (2019)

(untitled)
Geranylated 4-phenylcoumarins DMDP-1 and DMDP-2 isolated from Mesua elegans were elucidated for their role in inducing caspase-independent programmed cell death (CI-PCD) in prostate cancer cell lines, PC-3 and DU 145, respectively. The half maximal inhibition concentration value (IC50) identified through MTT assay of DMDP-1 is 13M for PC-3 cells, while DMDP-2 is 9M for DU 145 cells. Cell homeostasis disruption was demonstrated upon treatment, as shown by the increase in calcium ion through colourimetric assay and endoplasmic reticulum (ER) stress markers GRP 78 and p-eIF2 through western blot. Subsequently, cytoplasmic death protease calpain-2 also showed increased activity during DMDP-1 & -2 treatments, while lysosomic death protease cathepsin B activity was significantly increased in PC-3 treated with DMDP-1. Flow cytometry showed a reduction in mitochondrial membrane potential in both cell lines, while western blotting showed translocation of mitochondrial death protease AIF into the cytoplasm in its truncated form. Furthermore, DMDP-1 & -2 treatments caused significant increase in superoxide level and oxidative DNA damage. Concurrent inhibition of calpain-2 and cathepsin B during the treatment showed an attenuation of cell death in both cell lines. Hence, DMDP-1 & -2 induce CI-PCD in prostate cancer cell lines through calpain-2 and cathepsin B.